The pursuit of happiness, and other sobering thoughts - Will, George Francis 1884- (New York, N.Y. Harper & Row, Publishers, Inc., 1978)
Columns originally published in Newsweek and the Washington Post which deal with human nature and contemporary American life and politics.
"Originally published in Newsweek and the Washington post."
Includes index.
Keywords: Political culture -- United States; United States -- Social life and customs -- 20th century